1990
DOI: 10.1136/jech.44.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory illness in Adelaide children: breast feeding modifies the effect of passive smoking.

Abstract: Study objective-The aim was to investigate the relation between passive smoking and childhood acute respiratory illness.Design-The study involved an initial postal survey on a random sample of children followed by a case-control study based on the survey. A respiratory illness score was calculated from maternal reports of episodes of illness in the previous 12 months.Setting-The study was a population survey based on Adelaide metropolitan area in South Australia.Participants-The reference population (n= 13 996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
5

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 23 publications
6
53
0
5
Order By: Relevance
“…Focusing on infections between 7-12 months revealed a plausible time sequence supporting a true protective effect of breastfeeding. Our observation of a weaker effect of exposure to tobacco smoke products on LRTIs in long-term breastfed children, is consistent with results of a cross-sectional study of acute respiratory illness among children in Adelaide, Australia [29]. The results do not support a hypothesis that exposure to tobacco smoke products through breastmilk increases the risk of LRTIs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Focusing on infections between 7-12 months revealed a plausible time sequence supporting a true protective effect of breastfeeding. Our observation of a weaker effect of exposure to tobacco smoke products on LRTIs in long-term breastfed children, is consistent with results of a cross-sectional study of acute respiratory illness among children in Adelaide, Australia [29]. The results do not support a hypothesis that exposure to tobacco smoke products through breastmilk increases the risk of LRTIs.…”
Section: Discussionsupporting
confidence: 80%
“…The protective effect of breastfeeding has been difficult to establish. Results from developing countries are consistent with a protective effect of breastfeeding [16][17][18], while studies undertaken in industrialized societies have shown conflicting results [19][20][21][22][23][24][25][26][27][28][29][30][31]. There is recent evidence from a cross-sectional study of Australian children that breastfeeding protects from the adverse effects of passive smoking on acute respiratory illness [29].…”
supporting
confidence: 62%
“…Outros estudos também mostraram que o aleitamento natural é um fator de proteção para as infecções respiratórias 6,27,28 . Este efeito pode ser decorrente de uma combinação de mecanismos comportamentais, que podem produzir mudanças relacionadas à exposição da criança ao tabagismo domiciliar, e biológi-cos, por meio da aquisição de imunidade específica crescente para um maior grupo de vírus, que se observa quando a criança está sendo aleitada 29 .…”
Section: Discussionunclassified
“…In fact, Chen (22') and co-workers (28,29) reported an increased risk of acute respiratory illnesses in Chinese children living with smoking fathers in the absence of smoking mothers. Furthermore, Woodward and coworkers (30) found that children of smoking mothers were significantly more susceptible to acute respiratory illnesses even after mothers who smoked during pregnancy were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%